Evaluasi Kapasitas dan Tingkat Pelayanan Simpang Tiga Tak Bersinyal di Jalan Mergan Raya dan Jalan S. Supriyadi, Kota Malang - Nalius Aliva Royana Fitri; Yurnalisdel Yurnalisdel; Pamela Dinar Rahma (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
The performance of the unsignalized intersections at Jalan Mergan Raya and Jalan S. Supriadi in Malang City often experiences extreme traffic congestion, especially during rush hour. This study aims to provide a comprehensive examination of traffic patterns at these intersections and provide suggestions on how to improve them. This research uses a quantitative research design. Primary and secondary data were collected through direct surveys. The primary survey consisted of identifying side obstacles, calculating vehicle volume, and observing the physical form of the intersection. To learn more about population and vehicle growth, secondary data were obtained from the Malang City Statistics Agency (BPS). The 2023 Indonesian Road Capacity Guidelines (PKJI) were used to analyze the data, which included determining the degree of saturation (DJ), traffic volume, intersection capacity, delays, and the possibility of queues. The rate of vehicle growth was taken into account when forecasting intersection performance for the next five years. Based on the findings, the current intersection capacity is 3602 seconds per hour. Performance analysis shows a degree of saturation (DJ) of 1.04, indicating erratic traffic patterns and potential congestion. The potential for queuing ranges from 43.52% to 86.44%, with an average traffic delay of 17.52 seconds/vehicle. Traffic conditions are poor, as indicated by the current level of service (LOS), which is F. Traffic volume is expected to increase significantly over the next five years, with DJ reaching 1.70. This indicates that if corrective measures are not taken, intersection performance will continue to deteriorate and the LOS will remain at F. To improve intersection performance, this study recommends improving traffic signs and conducting additional research on the use of Traffic Signal Devices (APILL).